2014
DOI: 10.3109/01676830.2014.881398
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Isolated Bilateral Superior Orbital Vein Thrombosis as a Presenting Feature of Antiphospholipid Syndrome

Abstract: Although superior ophthalmic vein occlusion is rare, it is an important differential as orbital biopsy is to be avoided. This is only the second reported case secondary to antiphospholipid syndrome and the first such case with bilateral occlusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…[12][13][14][15][16] Other causes are hematologic like antiphospholipid syndrome, sickle cell disease, hormonal causes like tamoxifen, oral contraceptive pills etc, Tolosa-Hunt syndrome, idiopathic orbital inflammatory disease. [17][18][19][20][21][22][23][24][25] In a case series by Nicolien et al 3 the majority of the patients were aseptic (seven out of nine) although all the patients in this case series were adults. The septic causes were sinusitis, dental, orbital and facial infection.…”
Section: Discussionmentioning
confidence: 98%
“…[12][13][14][15][16] Other causes are hematologic like antiphospholipid syndrome, sickle cell disease, hormonal causes like tamoxifen, oral contraceptive pills etc, Tolosa-Hunt syndrome, idiopathic orbital inflammatory disease. [17][18][19][20][21][22][23][24][25] In a case series by Nicolien et al 3 the majority of the patients were aseptic (seven out of nine) although all the patients in this case series were adults. The septic causes were sinusitis, dental, orbital and facial infection.…”
Section: Discussionmentioning
confidence: 98%
“…[9][10][11][12][13] Hematologic aetiologies include antiphospholipid syndrome and sickle trait. [14][15][16][17] Also, hormone therapies have been reported as a cause for SOVT (e.g. tamoxifen, oral contraceptive pill).…”
Section: Discussionmentioning
confidence: 99%
“…There is a report of a female who developed bilateral SOVT 6 with associated peripheral retinal hemorrhages, on oral contraceptive pills. Idrees et al, 7 reported recently a case of bilateral SOV thrombosis secondary to antiphospholipid syndrome in a female with good vision along with associated disc swelling and proptosis. Our patient had good vision on presentation, with minimal orbital congestive signs; BCVA improved to 20/20 after treatment with anticoagulation and steroids.…”
Section: Discussionmentioning
confidence: 99%